Literatura, linguagem e dialogismo nos cristianismos primitivos: uma análise sêmio-discursiva em João 4.1-42 - Carvalho Júnior, Josemir José de (2022)
This research aims to contribute to a vast and promising methodological approach that relies on the interface between Bible and Literature, bringing the semio-discursive exegetical method to the text of the Community of the Beloved Disciple, specifically John 4:1-42. We understand this pericope to be significant for the Johannine community (and early Christianity as a whole) due to its carrying important communal values and identities. It is essential, therefore, to clarify the concepts of literature and the Bible on which we rely, as well as the assumptions we make about the early decades of the Jesus movement. We perceive this movement as a multiplicity of semiospheric environments, where memories and traditions interact, create, and recreate themselves in oral literature until they are consolidated in written form. Literary production is inherent to the origins of Christianity and occurs through the interaction of memories. Thus, fundamental aspects of language, such as the dialogism proposed by Mikhail Bakhtin, need to be considered in the analysis of these texts. Consequently, if we can make this connection, which has already been extensively explored in exegesis, it is worth proposing an investigation based on another Bakhtinian concept: polyphony. Here, polyphony refers not only to the combination of communal voices but also to how these voices are presented textually.(AU)